On the Behavior of Newly Synthesized Functionalized Imidazolium-Based Ionic Liquids for Highly Efficient Extraction and Separation of Pirimicarb from Orchard Real Wastewater - Sana Zulfiqar; Uzaira Rafique; M. Javed Akhtar; Hesham Hamad (Adsorption Science & Technology)
The presence of pirimicarb compounds as pollutants in orchard wastewater has sparked rising worries about their detrimental impacts on the ecosystem and human health, and their removal is critical for Pakistan’s aquatic environment. It not only contaminates fruit, but it also leaches into the soil and contaminates groundwater. However, there is little data on the effective removal of pirimicarb from orchard wastewater. The main purpose of this study is to create a novel family of functionalized imidazolium-based ionic liquids (ILs) using a simple chemical process, which will be utilized for the first time to extract pirimicarb from orchard wastewater in an efficient, cost-effective, and environmentally acceptable manner. FTIR, SEM, XRD, TGA, BET, and 1H NMR spectroscopy were used to characterize the functionalized samples. The impact of the IL substituent on the separation capacity was studied. In addition, the extraction and separation of pirimicarb from orchard wastewater were investigated under a variety of conditions (time, concentration, and temperature) in order to better understand the adsorption behaviors of distinct ILs in an aqueous solution. The adsorption equilibrium was reached in 30 minutes, and the maximum removal of pirimicarb was achieved utilizing the synthesized [C2im][C3H6NH2]Br-, according to the data. The pseudo-first-order model and the Langmuir model both suit well with the adsorption mechanism of pirimicarb with very good adsorptive capacities. Thermodynamic analyses indicated spontaneous, endothermic, and entropy-driven adsorption processes. The synthesized imidazolium-based ILs have good regeneration capability and recycling at least for six adsorption-desorption runs and have also been used to successfully detect pirimicarb orchard wastewater samples. The superior safety of the proposed method nominates it as a promising future strategy for pollution prevention. Consequently, this work has proven that the pirimicarb adsorption to various imidazolium-based ILs was dependent on the structures of the produced imidazolium-based ILs, which specifies its potential for practical applications in water pollutant removal and environmental remediation.